CEO, biến động dòng tiền và cấu trúc vốn của các doanh nghiệp niêm yết tại Việt Nam - Nguyen Hai , Yen (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This paper examines the impact of cash flow volatility on the capital structure in Vietnamese listed companies in the period 2008–2019. The system generalized method of moments is applied to investigate this relationship. The results show that there exists an inverse relationship between the volatility of cash flow and the capital structure in Vietnamese listed companies during the studied period. In particular, unlike previous studies on cash flow volatility, this study investigates the effect of the chief executive officer/director (CEO)’s financial experience on the relationship between cash flow volatility and capital structure. The results show that cash flow volatility has a positive impact on capital structure when CEOs have experience in finance field, whereas volatility of cash flow has a negative impact on capital structure when CEOs have not financial experience.
Keywords: Cash flow volatility; Capital structure; CEO; Financial experience